PERKEMBANGAN YAYASAN PENDIDIKAN AL-HUDA DI KOTA PEKANBARU (PERIODE 2003-2015) - Syakira Aini; Marwoto Saiman; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: Education as one of the most important sectors in the nationaldevelopment, be a mainstay for the work as much as possible in an effort to improve thequality of human life Indonesia, where faith and piety to God Almighty the source of lifein all areas. Therefore in this case the private education play an active role inpromoting education, especially in Pekanbaru with the establishment of educationalinstitutions under the auspices of the Education Foundation Al-Huda. The purpose ofthis study was to determine the background and Education Foundation Al-Hudafounding figures in the field of education, to know the developments in the field ofeducation Education Foundation Al-Huda period 2003-2015, to know the efforts madeEducation Foundation Al-Huda in the field of education, to know the factors drivingand inhibiting Education Foundation Al-Huda in its efforts promote education inPekanbaru. The method used is the historical method in which data were collectedthrough observation, interviews, documentation and literature. Data analysis usinghistorical writing. When the study began in the submission title until the completion of arevised proposal last essay writer. The results showed that Education Foundation Al-Huda formed on the notion character named Dr. H. Fachri Bais Salam Lc, MM whichformed Orphanage Isolated Tribe in 1986 and then grow until today EducationFoundation Al-Huda has overshadowed the five institutions that MTs Al-Huda, SMA Al-Huda, SMK Nasional Al-Huda, Akademi Keuangan dan Perbankan (AKBAR) danSekolah Tinggi Ilmu Ekonomi Riau (STIE-R). Based on these results it can be concludedthat Education Foundation Al-Huda is the body that houses the educational institutionsparticipating intellectual life of the nation. Education Foundation Al-Huda and fourthin its development agency has experienced growth in terms of both quantity and quality.Keywords: History, Development, Yayasan Pendidikan Al-Huda, Education2